Evaluasi Kebijakan Subsidi Pemerintah untuk Sektor Pendidikan Tinggi (1991-1996) - Muhadjir Effendy (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
Policy Assessment of Governmental Subsidies to Higher Education (1991-1996). Higher education is an important sector in preparing human resources as the actors of national development. Private universities have significant contributions to the sector, but state universities take the governmental subsidies more than private universities. The subsidies cause the state universities to be dependent. The government has to motivate the state universities to privatize their business. It should minimize its subsidies to the state universities and allocate the subsidies to other sectors, and should implement progressive ‘taxes’ for state students. On the other hand, the state universities have to improve their abilities to compete with the private universities as their competitors.